2019
DOI: 10.1159/000496034
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus B Tailors the Unfolded Protein Response to Favour Viral Amplification in Pancreatic β Cells

Abstract: Type 1 diabetes (T1D) is an autoimmune disease characterized by islet inflammation and progressive pancreatic β cell destruction. The disease is triggered by a combination of genetic and environmental factors, but the mechanisms leading to the triggering of early innate and late adaptive immunity and consequent progressive pancreatic β cell death remain unclear. The insulin-producing β cells are active secretory cells and are thus particularly sensitive to endoplasmic reticulum (ER) stress. ER stress plays an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 63 publications
1
29
0
Order By: Relevance
“…ER stress is often induced by viral infections, including CVB infections (Colli et al., 2019, Zhang et al., 2010). The type of these responses can vary depending on the cell type and the virus.…”
Section: Discussionmentioning
confidence: 99%
“…ER stress is often induced by viral infections, including CVB infections (Colli et al., 2019, Zhang et al., 2010). The type of these responses can vary depending on the cell type and the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, environmental cues, such as islet-tropic CVB infections, which are candidate environmental triggers for type 1 diabetes, may synergise with ER stress when stochastically coming together in time and space. Of note, recent findings suggest that CVBs use the UPR pathway IRE1α/XBP1s/JNK1 to foster their own replication in beta cells [17]. Further indirect support for the role of ER stress and environmental factors such as CVBs come from the observation that neighbouring alpha cells are spared by islet autoimmunity.…”
Section: Weakness 1: Making Insulin and Other Granule Proteins Is A Smentioning
confidence: 99%
“…Several viruses (including hepatitis C and hepatitis B viruses, Japanese encephalitis virus and human cytomegalovirus) can activate both UPR and the IRE1α/XBP1 pathway to facilitate their own replication [ 104 ]. In addition, a recent study revealed that CVB5 infection triggers the PERK and IRE1α branches of UPR in EndoC-βH1 and in the rat beta cell line, INS-1E [ 105 ]. Following CVB5 infection, a fully activated IRE1α/XBP1s pathway promoted phosphorylation and activation of JNK1, leading to an increase in viral replication and, ultimately, apoptosis.…”
Section: Ifns Induce Endoplasmic Reticulum Stress Unfolded Proteimentioning
confidence: 99%
“…Following CVB5 infection, a fully activated IRE1α/XBP1s pathway promoted phosphorylation and activation of JNK1, leading to an increase in viral replication and, ultimately, apoptosis. Conversely, siRNA mediated IRE1α knockdown or chemical inhibition of JNK1 reduced both responses [ 105 ]. Importantly, the pro-apoptotic and virus-activating effects of JNK1 were regulated independently.…”
Section: Ifns Induce Endoplasmic Reticulum Stress Unfolded Proteimentioning
confidence: 99%
See 1 more Smart Citation